2023
DOI: 10.1111/jace.18992
|View full text |Cite
|
Sign up to set email alerts
|

Lattice evolution and microwave dielectric properties of La‐doped yttrium aluminum garnet ceramics

Abstract: In this study, Y3−xLaxAl5O12 (0 ≤ x ≤ 0.09) ceramics were synthesized, and the phase composition, lattice evolution, and microwave dielectric properties were investigated in detail. Scanning electron microscopy confirms that the addition of moderate amounts of La2O3 improves the grain development of YAG ceramics, but excessive doping destabilizes the crystal structure. Transmission electron microscopy characterization shows that the variation of the dielectric properties of the samples with x‐value is related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In addition to the requirement for a high dielectric constant, other two key properties of the ceramics in the GHz frequency range are also highly concerned: a high quality factor ( Q × f , Q is approximately equal to 1/tan δ ) to improve selectivity and a near‐zero temperature coefficient of resonance frequency ( τ f ) to achieve temperature stability (most microwave devices applications require τ f ≤ ±10 ppm/°C) 5 . Previous studies have shown that even small variations in composition can dramatically affect the dielectric properties of ceramics, 6–8 suggesting the significant challenge of identifying the optimal composition for achieving the desired properties. Meanwhile, researchers have also noted the coupling relationship among ε r , Q × f , and τ f 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the requirement for a high dielectric constant, other two key properties of the ceramics in the GHz frequency range are also highly concerned: a high quality factor ( Q × f , Q is approximately equal to 1/tan δ ) to improve selectivity and a near‐zero temperature coefficient of resonance frequency ( τ f ) to achieve temperature stability (most microwave devices applications require τ f ≤ ±10 ppm/°C) 5 . Previous studies have shown that even small variations in composition can dramatically affect the dielectric properties of ceramics, 6–8 suggesting the significant challenge of identifying the optimal composition for achieving the desired properties. Meanwhile, researchers have also noted the coupling relationship among ε r , Q × f , and τ f 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rare earth oxides have been widely used in various fields due to their special electronic configurations and physicochemical properties 19–22 . Furthermore, microwave dielectric ceramics containing rare earth oxides had been intensively studied to explore promising microwave dielectric materials 23–26 . In this study, Re 2 O 3 (Re = Ho, Er, Tm) ceramics had been successfully prepared by solid‐phase reaction method, and the intrinsic influence mechanism of the microwave dielectric properties had been investigated using theoretical infrared spectra calculated by first‐principles.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Furthermore, microwave dielectric ceramics containing rare earth oxides had been intensively studied to explore promising microwave dielectric materials. [23][24][25][26] In this study, Re 2 O 3 (Re = Ho, Er, Tm) ceramics had been successfully prepared by solid-phase reaction method, and the intrinsic influence mechanism of the microwave dielectric properties had been investigated using theoretical infrared spectra calculated by first-principles. Meanwhile, phonon spectra, density of states, and electronic localization functions were calculated together to analyze the dynamical stability and electronic structure of Re 2 O 3 (Re = Ho, Er, Tm) ceramics.…”
Section: Introductionmentioning
confidence: 99%